(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the problems encountered by patients wearing newly made complete dentures. Study Design: A Cross Sectional Survey Place and Duration of Study: This study was conducted at the Department of Prosthodontics at Liaquat College of Medicine and Dentistry, Karachi from January 2018 to June 2018. Materials and Methods: A total 95 patients were required according to the sample size calculated by Raosoft calculator. All newly complete denture wearing patients were selected by consecutively sampling method. Patient records were checked for their ages, gender, medical history, and associated debilitating conditions that they might be suffering from. Statistical analysis of all the data was performed using SPSS version 21. Results: A total of 95 patients, 52 were females and 43 were males. The age ranged from 60 to 80 with the average age being 72 + 8 years. The results show that women complain more about dentures than men. The most prevalent issues included sore spots and ulcers in the mandible (60%) and maxilla (29.4%) regions, generalized discomfort (55.7%), and denture instability (55.7%). Esthetic concerns such as fullness under the nose (40%), speech problems (33.6%), and functional interference during swallowing/chewing (41%) were also reported. Conclusion: The study findings highlight the need for improved denture design and fitting techniques to enhance patient satisfaction and reduce discomfort among denture wearers, particularly in the female population.